Given A,B,C are sets and g: A -> B, f: B -> C.

I've been at this for a while now while also focusing on similar problems. I'm thinking a contradiction what be easiest suited.

So far,

Suppose f o g is surjective, g is not surjective and with the view to contradiction, suppose f is injective.

Since g is not surjective, we know there exists some b in B such that for all a in A, g(a) != b.

Moreover, since f is injective, for all b, b' in B such that b != b' => f(b) != f(b').

let c be in C, such that c = f(b), but there exists no g(a) = b, and given there exists a c that has no a such that (f o g)(a) = c, this opposes our assumption that f o g is surjective.

This is a contradiction, so f is not injective.


It is correct. I would do a direct approach: if $f\circ g$ is surjective and $g$ is not surjective, you want to prove that $f$ is not injective. Take $b\in B$ wich doesn't belong to the image of $g$ and take $a\in A$ such that $f\bigl(g(a)\bigr)=f(b)$. But $b\neq g(a)$. Therefore, $f$ is not injective.


without using elements:

the image $f \circ g(A) \subseteq f(B)$. So, if $f \circ g (A)=C$, then $f$ better be surjective as well. If $f$ were a bijection, then there is an inverse $f^{-1}$. Then $f(g(A))=C=f(B)$. Apply the inverse to both sides of this equation.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.